Syphilis? An Unusual Cause of Surgical Emergency in a Human Immunodeficiency Virus-Infected Man. (20th June 2015) - Bender Ignacio, Rachel A.; Koch, Lisa L.; Dhanireddy, Shireesha; Charmie Godornes, B.; Lukehart, Sheila A.; Marrazzo, Jeanne M.
Abstract: We report on a human immunodeficiency virus-infected man undergoing urgent anorectal surgery, with multi-centimeter fungating masses discovered inside the anus. Initial pathology was inconclusive. After the patient developed a disseminated rash postoperatively determined to be secondary syphilis, the anorectal pathology was reviewed and Treponema pallidum DNA was amplified by polymerase chain reaction from the mass.